1997
DOI: 10.2337/diab.46.9.1393
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Induces In Vivo Adipocyte Differentiation in the Obese Zucker fa/fa Rat

Abstract: Thiazolidinediones are potent antidiabetic compounds, in both animal and human models, which act by enhancing peripheral sensitivity to insulin. Thiazolidinediones are high-affinity ligands for peroxisome proliferator-activated receptor-gamma, a key factor for adipocyte differentiation, and they are efficient promoters of adipocyte differentiation in vitro. Thus, it could be questioned whether a thiazolidinedione therapy aimed at improving insulin sensitivity would promote the recruitment of new adipocytes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 0 publications
9
51
1
1
Order By: Relevance
“…Moreover, it has been reported the expression of FABP3 was positively correlated with the IMF content (Cho et al, 2011), thus the increased IMF levels in the TZD group could be associated with the up-regulated expression of FABP3. There was no difference in the mRNA abundance of GLUT4 between the control and TZD groups, which was inconsistent with the findings of other researches (Hallakou et al, 1997; Miyazaki et al, 2002). It suggested TZD had no effect on glucose utilization when it was supplemented for healthy animals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported the expression of FABP3 was positively correlated with the IMF content (Cho et al, 2011), thus the increased IMF levels in the TZD group could be associated with the up-regulated expression of FABP3. There was no difference in the mRNA abundance of GLUT4 between the control and TZD groups, which was inconsistent with the findings of other researches (Hallakou et al, 1997; Miyazaki et al, 2002). It suggested TZD had no effect on glucose utilization when it was supplemented for healthy animals.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, TZD supplementation increased the mRNA abundance of FABP3 mRNA by 65.12% above that of the control group, indicating an up-regulated transport and accretion of fatty acids in the muscle of TZD-fed animals. This is consistent with the findings of Hallakou (1997) showing that a TZD treatment of the obese Zucker rat induced a marked increase in weight gain, and stimulated the expression of genes necessary for lipid metabolism. Moreover, it has been reported the expression of FABP3 was positively correlated with the IMF content (Cho et al, 2011), thus the increased IMF levels in the TZD group could be associated with the up-regulated expression of FABP3.…”
Section: Discussionsupporting
confidence: 92%
“…The capacity of TZDs to ameliorate insulin resistance is typically attributed to their ability to activate PPARγ and promote adipogenesis [24], [25]. By enhancing the formation of new adipocytes, TZDs are thought to drive triacylglycerol storage in adipose tissues, reduce circulating lipid levels and prevent lipid accumulation and toxicity in other insulin-sensitive tissues [1].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study showed that pioglitazone was also effective for alcoholic steatohepatitis in rats without altering insulin sensitivity (20). Pioglitazone promotes the differentiation of pre-adipocytes into adipocytes (2123) and may result in the redistribution of triglycerides from the liver into proliferating adipocytes. Pioglitazone is generally known to cause weight gain as an adverse effect, which is supported in this case as the patient gained 8 kg of body weight.…”
Section: Discussionmentioning
confidence: 99%